ANÁLISE ERGONÔMICA DO TRABALHO EM UMA PAMONHARIA - DAMAS, CARMEN APARECIDA; DE OLIVEIRA MAGALHÃES, DANIELA; COSTA ARAÚJO, GABRIELA CRISTINA; DE SENA CAZUZA, LUIZ HENRIQUE; CIRILO, TIAGO MAGNO; COLAMARCO FERREIRA RESENDE, MÁRCIA (Sinapse Múltipla, 2019)